HUBUNGAN KEBISINGAN MESIN DIESEL DENGAN KESELAMATAN KERJA NELAYAN DI DESA KOMBANG KECAMATAN TALANGO - Syaifurrahman Hidayat; Nurul Qamariyah (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2017)
Work health and safety is one of the protection labor by means of application technology control all aspects potentially harmful workers.Noise is one of the factors environment by the accident work. This research is analytic observational research with cross sectional approach.The population in this research has reached 1128 workers fishermen with the total sample 69 workers. Sampling techniques used in this research is simple random sampling and analysis used is the rank spearman worth value α=0,05. Free variable in this research is noise and bound variable namely is occupational safety, and instruments used is a questionnaire. this research aims to analyze relations noise a diesel engine with occupational safety fisherman in Desa Kombang Kecamatan Talango. The results of the study is the majority of workers feel not noisy of the diesel engines while working as many as 46 workers (67 %) And most of all workers with good safety working as many as 67 workers (97 %). The correlation noise diesel engines with occupational safety fishermen in Desa kombang Kecamatan Talangotahun 2106. Working environment is one of the main source of potential danger work safety and health , one of the factors that contained in the workplace is noise.Noise work in frequently its own problems for labor , mostly comes from a work , but many workers who are familiar with noise. Because of that workers to avoid from an accident due to work should always be providing and used a protective.